RENIN, ERYTHROPOIETIN AND VITAMIN D RELEASE FROM HUMAN DONOR KIDNEYS DURING NORMOTHERMIC MACHINE PERFUSION: PREDICTORS OF POST-TRANSPLANTATION OUTCOME?. (June 2022) - Lin, Hui; Du, Zhaoyu; Bouari, Dafsy; Rijkse, Elsaline; Jan Danser, A.H.; Minnee, Robert; Hoogduijn, Martin
Abstract : Objective: Normothermic (37C) machine perfusion (NMP) is a potential alternative to currently used hypothermic (4C) machine perfusion (HMP) for donor kidney preservation before transplantation. NMP allows for metabolic activity and for functional assessment of donor kidneys. The kidneys are key producers of hormones and we investigated the release of prorenin/renin, erythropoietin (EPO), and vitamin D by kidneys on machine perfusion. Design and method: Ten donor kidneys were subjected to HMP followed by 2 h of oxygenated NMP before transplantation. NMP perfusate was collected at three time points (0 h, 1 h, 2 h). Ten HMP perfusate samples were collected for the same measurements. Results: Median release rates of prorenin (196 [i.q.r 28–266] ng/hour) and renin (228 [94–302] ng/hour) in the first hour of NMP were 83- and 37-fold higher than that in HMP perfusates respectively (p = 0.0009 and p < 0.0001). Median renin release rate showed a 3.2-fold downregulation during the second hour of NMP compared to the first hour. Median EPO release rate (14 [i.q.r 8–48] mIU/min) during the first hour of NMP was 2.9-fold higher than that in HMP perfusates (p = 0.035), while it remained stable in the second hour of NMP. Active vitamin D was undetectable in HMP perfusate samples, while there was a median vitamin D secretion of 56 (i.q.r 30–83) and 28 (8–50) pmol/hour in the first and second hour of NMP respectively (p = 0.0001 and p = 0.003). We then investigated whether there were correlations between the hormone releasing capacity and donor kidney status. Prorenin release rate in the second hour of NMP was lower as cold ischemia time (CIT) until NMP of donor kidneys increased (r = -0.605; p = 0.049). EPO release showed no correlation with donor age or CIT. Donor age and vitamin D release rate during two hours of NMP are highly correlated (r = 0.652; p = 0.034). Interestingly, donation after brain death (DBD) kidneys significantly released more vitamin D than donation after circulatory death (DCD) kidneys during the first and second hour of NMP (p = 0.024 and p = 0.012). Conclusions: These data shows that NMP increases the hormone release capacity of transplant kidneys. Hormone release may represent a tool to assess kidney function during NMP.